KONSEP DIRI REMAJA DALAM FILM INDONESIA: ANALISIS WACANAATAS FILM REMAJA INDONESIA TAHUN 1970-2000-AN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Film is a system of representation, which provides information of social dynamics during the period, when the film is produced and distributed. This study is aimed to identify and reveal how teenage selfconcept is discursively constructed through film imagery and narrative in the context of Indonesian society. This study focuses particularly on the physical and psychological teenage self-concept. Corpus of analysis are eight teenage films which were produced in the period of 1970s to the 2000s. By applying Norman Fairclough's critical discourse analysis, the close examination of the teenage films reveals that there are similarities, modification and differences in the way in which teenage self-concept has been constructed from decade to decade. This study also identifies that teenage self-concept has been constructed through various discourses, among other things, through discourse of good vs'bad teenager, of role model seeking and of teenage lifestyle.